Keterjalinan Jampé, Jangjawokan, dan TOGA dalam Naskah Mantra Pengobatan: Peran dan Fungsinya di Masyarakat Adat - Sumarlina, Elis Suryani Nani; Permana, Rangga Saptya Mohamad; Darsa, Undang Ahmad (Kamaya: Jurnal Ilmu Agama, 2025)
A Sundanese manuscript, created by the ancestors' inventiveness, is a cultural document containing local wisdom. The Medical Mantra Manuscript is one of them. It reveals the truths of numerous TOGA as well as the presence of mantras in an effort to overcome and cure various diseases in society. Sundanese Mantra is classified into the following categories: ajian, asihan, jampé, jangjawokan, pélét, rajah, and singlar. This research, however, solely looks at the interweaving of the texts of the Mantra Jampé and Jangjawokan with TOGA, whose duties and functions are still practiced by indigenous peoples in West Java and indigenous Baduy people in Banten. The descriptive analysis research method was used. Involve philological study methods, both codicological and textological, literary studies, and cultural studies, so that the results are helpful and serve as a literacy reference for other disciplines. The utilization of plant species, functions, dosages, methods of processing, and treatments done accompanied by the recital of'mantras' in the text of the Medicinal Manuscripts demonstrates the relationship between Jampé and Jangjawokan and TOGA. The findings of this study are expected to be valuable not only for literature and philology, but also for public health, pharmacy, nursing, medicine, communication science, literature, anthropology, and culture in general.